Effect of Toxicity of Phthalate Esters during Early Vertebrate Development of Zebrafish (Danio rerio) - Mohamad Shamil Faris, Mohamad Khalid (Universiti Malaysia Sarawak (UNIMAS), 2018)
Dially I phthalate (DAP) and dipropy I phthalate (DPP) belong to a group of chemicals called phthalate esters (P AEs) which are commonly used as plasticisers. However, higher temperature of the environment is able to break the weak bond of the weak bonding between these chemical with polyvinyl chloride (PVC) allow it to leak into the environment. These two chemical was listed as carcinogenicity and endocrine disrupting potentials. This study was set out to study the LCso and the morphological d feet of DAP, DPP and DPP+DAP chemical on zebrafish embryonic development. Toxicity of the chemicals is determined by using pro bit analysis. The LC50 are measured at 96 hpf. Morphological defect sllch as unhatched, pericardia edema, yolk sac edema, uninflated swim bladder and tail defonnation, which were measured at 96 hpf. The LCso was determined to be at 6.58 mg/I for DPP, 5.12 mg/I for DAP and 1.71 mg/I for 0 P+DPP with 95% confidence level. The LClO was determined to be at 3.80 mg/I for DPP, 3.60 mgll for DAP, 0.92 mg/l for DAP + DPP with 95% confidence level. The thyroid hormone (TH) gene marker used in this study are; diodinase I(dio_l), diodinase 2(dio_2), Tli receptor alpha (Iro), TH receptor beta (trfJ), thyroid stimulating honnone beta (tshjJ) and transthyreiin (ttr). This study demonstrated that DPP, DAP, DPP+DAP indllced developmental toxicity, impaired the structure and functions of developing organ, and altered the expression of the thyroid hormone gene marker.